Implikasi Gaya Kepemimpinan Kepala Madrasah Perempuan terhadap Kualitas Manajemen di Madrasah Aliyah Assulamy Langko Desa Langko Kecamatan Lingsar Kabupaten Lombok Barat - Rohilawati Aini; Fathurrahman Fathurrahman; Alkusaeri Alkusaeri (LP2M STIT Palapa Nusantara, 2023)
This study aims to determine the Implications of the Leadership Style of Female Madrasah Principals on Management Quality at MA Assulamy Langko. Using a qualitative-descriptive approach, data collection techniques using observation, interviews and documentation. This study found that the head of MA Assulamy Langko applied a democratic, authoritarian and situational leadership style. The application of each type of leadership is applied at a certain time. The democratic type is applied in decision making at meetings, the autocratic style type is applied when there is a teacher who continuously violates it so that the madrasah head has his own decision/assessment of the teacher, while the situational type is applied according to the conditions of the teacher, staff and the surrounding environment. Meanwhile, the quality of management at MA Assulamy Langko can be said to be good because the head of the madrasa together with the deputy head of the madrasa and all the teachers work together in improving the quality of management in the madrasa. And the implications of the leadership style of the female principal at MA Assulamy Langko can gradually increase the motivation and discipline of teachers and students.